The Molecular Biology of Pancreatic Cancer - Abramson, Michael A. (International Society of Gastrointestinal Oncology, 2007)
Pancreatic cancer is the fourth leading cause of cancer-related death in the United States. It is a highly aggressive malignancy for which currently available treatments are of only limited efficacy. For this reason, much research is directed at elucidating fundamental molecular mechanisms underlying the biology of pancreatic cancer. These efforts are generating a rapidly growing body of information. The yet unmet challenge is to translate this information into clinically applicable strategies for early detection, prediction of prognosis, and effective therapies for patients diagnosed with pancreatic cancer.